The foundation of knowledge management: a review from conventional and Islamic perspectives - Hj. Yaakub, Muhamadul Bakir; Othman, Khatijah (UniversityPublications.net, 2014)
Globalizations bring challenges for an organization to adopt a comprehensive scientific culture in their exploitation of emerging sciences and knowledge. This is vital in order to update its development, and techniques use in taking care of potential human resources for organizational survival and development. This paper is an effort to address the prospect of knowledge management (KM) and postulate an idea for its critical foundation and effective action to overcome any issues in KM application from Islamic perspective, especially in dealing with multi-dimensional aspects and categories of human knowledge, its function and utilization. This is achieved through observing the sources of KM references both in conventional and Islamic literatures. This has been done for accessing the description of knowledge within the theoretical and organizational context. No doubt the issue of knowledge management (KM) represents an ultimate basis of growth and progress, whether at individual or society, as well as organizational level. Hypothetically, when we manage our knowledge, we will be able to consider it’s behavioral and functions in achieving our development, prosperous and growth. Subsequently, it is also intuitive to wonder the vice versa.